A Review of The Opportunities and Challenges in Digital-Based Mosque Management - Wahyuningsih, Sri; Anggraini, Novita Dwi Silvia; Reviyanti, Reni; Masuwd, Mowafg Abrahem (International Tatho Academics, 2025)
The advancement of technology through digital media has influenced mosques in Indonesia, including the Great Mosque of Kudus located in Kudus, Central Java Province, Indonesia, in conducting digital-based da'wah. E-da'wah has become an effective method of disseminating Islamic teachings in today's era, particularly among the millennial generation. This study aims to examine the implementation of digital-based management (e-da'wah) at the Great Mosque of Kudus. The research employed a qualitative approach, with data collected through interviews, observations, documentation, and relevant literature. The findings reveal that the Great Mosque of Kudus conducts digital da'wah through live streaming on social media platforms such as YouTube and Facebook to make religious content more accessible to the public. The opportunities include attracting greater public participation in mosque development, enhancing the mosque’s visibility, and enabling the permanent dissemination of Islamic knowledge. However, the challenges involve the risk of content misuse by irresponsible individuals and the need for continuous innovation by utilizing the full features of digital platforms. These findings imply that mosque administrators should optimize digital-based management such as through websites and Instagram by actively involving Muslim youth in Kudus.